The Influence of POC Empty Bunch and NPK 17+17+17 Fertilizer on The Growth and Production of Long Bean Plants - Robert Harianja (Postgraduate, University of Mataram, 2026)
The research was conducted from June to August 2023 in Nagori Sah Kuda Bayu Pasar Baru at an altitude of ± 136 m above sea level. The purpose of the research is to determine the effect of Empty Fruit Bunches (Janjang) and NPK fertilizer on the growth and production of long bean plants (Vigna sinensis L.). This research was conducted using a factorial randomized block design (RBD), consisting of two factors: The first factor is the application of Empty Bunches, which consists: T0=without the application of empty bunches, T1=2.4kg/plot, T2=4.8kg/plot, and T3=7.2kg/plot. The second factor is the addition of NPK fertilizer doses N0=without NPK fertilizer, N1=24g/plot, N2=48g/plot, N3=72g/plot. The parameters observed in this study include: Number of Leaves (Sheets) and Plant Height (cm) at 2, 4 and 6 WAP, Number of Fruits Per Sample Plant (Pods), Weight of Fruits Per Sample Plant (g), and Weight of Fruits Per Plot (kg). The research results indicate that the NPK 17+17+17 treatment significantly affected the Number of Leaves, Plant Height, Number of Fruits per Plant, Weight of Fruits per Plant, and Weight of Fruits per Plot. The best dose of NPK fertilizer 17+17+17 is 150 kg/ha (72 g/plot).